Perceived Stress and Nomophobic Behavior Among Junior Medical Students in Russia And Uzbekistan - Evgeni NIKOLAEV; Igor POVERINOV; Laziz NIYAZOV (Communications of International Proceedings, 2020)
The paper presents the results of a study of the features of manifestation of nomophobic behavior and its interrelationships with perceived stress in junior medical students from two countries with different cultures. The anonymous survey using the FIE-Stress Inventory and Mobile phone use related anxiety questionnaire was attended by 292 students in the first two years of study - 210 students from Ulianov Chuvash State University in Cheboksary and 82 -from Bukhara State Medical Institute. The data on the similarities and differences among students of Russia and Uzbekistan in the level of stress, manifestations of nomophobic behavior and their interconnections which can be taken into account when planning preventive work with students at a medical university were obtained.
Keywords: medical students; stress; nomophobia; Russia; Uzbekistan